Simulation of ADSL modem using MATLAB / Saiful Anwar Zulkarnain - Zulkarnain, Saiful Anwar (2005)
This thesis, is mainly focused at 256 Channel ADSL modem model in MATLAB software. This thesis highlights the simulation of ADSL by using Discrete Multitone(DMT) signaling modulation technique, which is a method that divides the copper line in smaller frequency bands and analyze signal that can show the bit allocation vector constellations in a graphical way, magnitude response for with and without error correction and performance of Quadrature Amplitude Modulation (QAM).The result that were obtained through these analysis showed that the precise and accurate of any system can be achieved by simulation software, therefore MATLAB is chosen in designing, simulating, testing and analyzing the system.